Coupling chemical looping air separation with the Allam cycle – a thermodynamic analysis - Saqline, Syed (2023)
The Allam cycle is a class of oxy-fuel combustion power cycles using supercritical CO2 (s-CO2) as the thermal fluid to achieve power generation with inherent capture of CO2. Compared to other conventional CO2 capture techniques, the Allam cycle stands out owing to its high fuel-to-electricity conversion efficiency (55–59%), the elimination of the Rankine cycle and reduced physical footprint. A key source of energy penalty of Allam cycle comes from the air separation unit (ASU), which supplies pure oxygen via an energy intensive cryogenic process. This paper presents a thermodynamic analysis of a novel supercritical CO2-based power generation scheme, in which a natural gas fuelled Allam cycle is integrated with a chemical looping air separation (CLAS) system, which supplies oxygen to the combustor. The modelling results show that the Allam-chemical looping air separation (Allam-CLAS) process can achieve 56.04% net electrical efficiency with a 100% CO2 capture rate, when a Co3O4-based oxygen carrier is used. This is 6% higher than the Allam cycle coupled to a cryogenic ASU. The exergetic efficiency of the Allam-CLAS system driven by the Co3O4-CoO redox cycle is 57.13%, also more favourable than a conventional Allam-ASU system (with reported exergetic efficiency of 53.4%). This newly proposed Allam-CLAS power cycle presents a highly efficient, and simple solution to generate zero-carbon electricity from natural gas.